KORELASI KEKUATAN OTOT LENGAN TERHADAP AKURASI SMASH PEMAIN BADMINTON PB. AHS - Cyntia Anggraini; Mawardi Nur; M. Fauzan Ritonga; Vita Tanti Imelda Rumahorbo (STKIP Subang, 2026)
This study aims to examine the correlation between arm muscle strength and smash accuracy in badminton players through a systematic literature review approach. The smash is a primary attacking technique in badminton that requires a combination of strength, coordination, speed, and precision. Data were collected by reviewing relevant books, journals, and scientific publications, which were subsequently analyzed and classified according to the research needs. The results indicate a significant positive correlation between arm muscle strength and smash accuracy among badminton players. Players with greater arm muscle strength tend to produce more powerful, faster, and more accurate smash shots. Physiologically, improvements in arm muscle strength through structured training such as push-ups, pull-ups, and resistance training have been shown to enhance muscular force production, directly impacting smash precision. Beyond arm muscle strength, smash accuracy is also influenced by hand-eye coordination, mastery of basic techniques, wrist flexibility, and the regularity of training. It is concluded that the higher the arm muscle strength of a player, the better their ability to produce accurate and effective smashes.